Female gender is associated with long COVID syndrome: a prospective cohort study. (April 2022) - Bai, Francesca; Tomasoni, Daniele; Falcinella, Camilla; Barbanotti, Diletta; Castoldi, Roberto; Mulè, Giovanni; Augello, Matteo; Mondatore, Debora; Allegrini, Marina; Cona, Andrea; Tesoro, Daniele; Tagliaferri, Gianmarco; et al.
Abstract: Objective: We explored the association between female gender and long COVID syndrome, defined as persistence of physical and/or psychological symptoms for more than 4 weeks after recovery from acute COVID-19 disease. The secondary aim was to identify predictors of long COVID syndrome by multivariable logistic regression analysis. Methods: This was a single-centre prospective cohort study conducted at San Paolo Hospital in Milan, Italy. We enrolled adult patients who were evaluated at the post-COVID outpatient service of our Infectious Diseases Unit between 15 April 2020 and 15 December 2020. Participants were individuals who had clinically recovered from COVID-19 and in whom virological clearance had occurred. Previous infection by SARS-CoV-2 was microbiologically documented by positivity using a reverse-transcriptase polymerase chain reaction (RT-PCR) assay of nasopharyngeal swab. All enrolled patients underwent blood tests and a comprehensive medical examination at follow-up. Individuals were interviewed about resolved and persisting symptoms and were asked to fill in two questionnaires to allow assessment of the Hospital Anxiety and Depression symptoms (HADS) score and of the Impact of Event Scale–Revised (IES-R) score. Results: A total of 377 patients were enrolled in the study. The median time from symtpom onset to virological clerance was 44 (37–53) days. A diagnosis of long COVID syndrome was made in 260/377 (69%) patients. The most common reported symptoms were fatigue (149/377, 39.5%), exertional dyspnoea (109/377, 28.9%), musculoskeletal pain (80/377, 21.2%) and "brain fog" (76/377, 20.2%). Anxiety symptoms were ascertained in 71/377 (18.8%) individuals, whereas 40/377 (10.6%) patients presented symptoms of depression. Post-traumatic stress disorder (defined by a pathological IES-R score) was diagnosed in one-third of patients (85/275, 31%). Female gender was independently associated with long COVID syndrome at multivariable analysis (AOR 3.3 vs. males, 95% CI 1.8–6.2, p < 0.0001). Advanced age (adjusted (A)OR 1.03 for 10 years older, 95% CI 1.01–1.05, p 0.01) and active smoking (AOR 0.19 for former smokers vs. active smokers, 95% CI 0.06–0.62, p 0.002) were also associated with a higher risk of long COVID, while no association was found between severity of disease and long COVID (AOR 0.67 for continuous positive airway pressure (CPAP)/non-invasive mechanical ventilation (NIMV)/orotracheal intubation (OTI) vs. no 02 therapy, 95% CI 0.29–1.55, p 0.85). Discussion: Factors that were found to be associated with a higher risk of developing "long COVID" syndrome were female gender, older age and active smoking, but not severity of the acute disease. Individuals affected by SARS-CoV-2 infection with the aforementioned features should be early identified and involved in follow-up programmes.